An Econometric Analysis of Countries' Repayment Performance to the International Monetary Fund - Aylward, Lynn (IMF Working Papers; Working Paper, 1998)
While the literature on external debt repayment performance by sovereign debtors is extensive, repayment performance vis-a-vis the International Monetary Fund has not been dealt with separately. Given differences between the Fund and other providers of financial resources, this paper considers whether it is possible to distinguish through logit analysis between the countries that make timely repayments to the Fund and those that become overdue. The paper finds that the inclusion of Fund-specific financial variables and a small number of macroeconomic variables yields a highly significant econometric model of the probability of a country incurring Fund arrears.